2022
DOI: 10.3389/fgene.2022.952689
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antibiotic profile, virulence determinants, ESBLs, and non-β-lactam encoding genes of MDR Proteus spp. isolated from infected dogs

Abstract: This study investigated the prevalence, antibiogram, virulence, extended-spectrum β-lactamases (ESBLs), and non-β-lactam encoding genes of Proteus species isolated from infected dogs in Ismailia province, Egypt. The study was conducted on 70 fecal swabs collected from dogs with diarrhea for bacteriological identification of Proteus spp. The positive isolates were evaluated for antibiotic susceptibility, molecular tests of virulence, ESBLs, and non-β-lactam encoding genes. Prevalence of Proteus spp. was 35.7% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The escalating emergence of MDR strains of P. mirabilis underscores the pressing need to discover new and effective approaches for combating microbial infections ( Algammal et al., 2021 ; Kang et al., 2021 ; Li et al., 2022 ). The emergence of MDR P. mirabilis strains in dogs presents a significant public health concern, particularly due to the close relationship between dogs and humans ( Decôme et al., 2020 ; El-Tarabili et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The escalating emergence of MDR strains of P. mirabilis underscores the pressing need to discover new and effective approaches for combating microbial infections ( Algammal et al., 2021 ; Kang et al., 2021 ; Li et al., 2022 ). The emergence of MDR P. mirabilis strains in dogs presents a significant public health concern, particularly due to the close relationship between dogs and humans ( Decôme et al., 2020 ; El-Tarabili et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous reports have confirmed that certain microbial species produced extended-spectrum β-lactamases (ESBLs), the hydrolytic enzymes, that confer the microorganisms’ resistance towards the lactam-based antibiotics by their degrading act on the β-lactam ring of the antibiotics class, i.e., penicillins, cephalosporins, cephamycins, monobactams, carbapenems, and carbacephems. Some of the other approaches in structural modifications by the microorganisms also include acyl-transfer, phosphorylation, glycosylation, nucleotidylation, ribosylation, as well as thiol transfers [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%